Impact of the introduction of chikungunya and zika viruses on the incidence of dengue in endemic zones of Mexico. - Larissa Fernandes-Matano; Irma Eloisa Monroy-Muñoz; Hector Daniel Pardavé-Alejandre; Luis Antonio Uribe-Noguez; María de Los Angeles Hernández-Cueto; Teresita Rojas-Mendoza; Clara Esperanza Santacruz-Tinoco; Concepción Grajales-Muñiz; José Esteban Muñoz-Medina (Public Library of Science (PLoS), 2021)
Background With the arrival of chikungunya (CHIKV) and zika (ZIKV) viruses in Mexico, there was a decrease in diagnosed dengue virus (DENV) cases. During the first years of cocirculation (2015-2017), the algorithms established by epidemiological surveillance systems and the installed capacity limited us to one diagnostic test per sample, so there was an underestimation of cases until September 2017, when a multiplex algorithm was implemented. Therefore, the objective of this study was determine the impact of the introduction of CHIKV and ZIKV on the incidence of diagnosed DENV in endemic areas of Mexico, when performing the rediagnosis, using the multiplex algorithm, in samples from the first three years of co-circulation of these arboviruses. Methodology and principal findings For this, 1038 samples received by the Central Laboratory of Epidemiology between 2015 and 2017 were selected for this work. Viruses were identified by multiplex RT-qPCR, and the χ2 test was used to compare categorical variables. With the new multiplex algorithm, we identified 2.4 times the rate of arbovirosis as originally reported, evidencing an underestimation of the incidence of the three viruses. Even so, significantly less dengue was observed than in previous years. The high incidence rates of chikungunya and Zika coincided with periods of dengue decline. The endemic channel showed that the cases caused by DENV rose again after the circulation of CHIKV and ZIKV decreased. In addition, 23 cases of coinfection were identified, with combinations between all viruses. Conclusions and significance The results obtained in this study show for the first time the real impact on the detected incidence of dengue after the introduction of CHIKV and ZIKV in Mexico, the degree of underestimation of these arboviruses in the country, as well as the co-infections between these viruses, whose importance clinical and epidemiological are still unknown.